Le Musée instrumental du Conservatoire de Paris pendant la décennie Lang (1981-1993) - Florence Gétreau (In Situ)
Responding to its initial vocation as a "complete collection of instruments for our use, which by their perfection can serve as models", the Instrumental Museum of the Paris Conservatoire really opened up to instrument makers in 1961, when Geneviève Thibault de Chambure, its curator, founded a restoration workshop there. Several generations of instrument makers have since sought knowledge and inspiration from these collections. Twenty years later, the museum team and its restorers have established a dialogue with this specialized public, eager to study reliable sources for interpreting repertoires that were not solely those of written music. The arrival of Jack Lang and Maurice Fleuret was particularly favorable to the development of this cooperation. The museum team was instrumental in drawing up the 21 measures of the "Plan de relance de la facture instrumentale" ("Plan to revive instrument making"), and spurred the creation of the CERDO (Centre de recherche et de documentation organologique), now part of the Philharmonie de Paris media library. Many instrument makers have come to explore the Conservatoire's collections. Doubtless because of their encyclopedic and multicultural nature, they have enabled a borderless approach, bearing witness to instrumental practices circulating between the learned and the popular. Having worked for twenty years at the Musée Instrumental and ten at the Musée des Arts et Traditions Populaires (MNATP), I offer here an essay in critical heritage historiography, in which instrument making contributes to the practice of oral music.